Reflective photomask blank and reflective photomask

KR103020388B1Active Publication Date: 2026-09-16테크센드포토마스크가부시키가이샤
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020247016802
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-11-24
Filing Date
2022-11-22
Publication Date
2026-09-16
Estimated Expiration
2042-11-22

Smart Images

  • Figure 112024054574836-PCT00002_ABST
    Figure 112024054574836-PCT00002_ABST
Patent Text Reader

Abstract

The present disclosure aims to provide a reflective photomask blank and a reflective photomask having high transferability (especially resolution) and maximizing the use of the phase shift effect. A reflective photomask blank (100) according to one embodiment of the present disclosure comprises a substrate (11), a reflective layer (12) that reflects EUV light having a multilayer film structure formed on the substrate (11), a protective layer (13) formed on the reflective layer (12) to protect the reflective layer (12), and an absorbing layer (14) that absorbs EUV light formed on the protective layer (13), wherein the absorbing layer (14) has a phase difference within the range of 200 degrees or more and 280 degrees or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to a reflective photomask blank and a reflective photomask. Background Technology

[0002] In the manufacturing process of semiconductor devices, the demand for miniaturization of photolithography technology is increasing along with the miniaturization of semiconductor devices. The minimum development dimensions of a transfer pattern in photolithography depend greatly on the wavelength of the exposure light source, and the shorter the wavelength, the smaller the minimum resolution dimensions can be. For this reason, the exposure light source in the manufacturing process of advanced semiconductor devices has been replaced from the conventional ArF excimer laser light with a wavelength of 193 nm to EUV (Extreme Ultraviolet) with a wavelength of 13.5 nm.

[0003] Since most materials have high light absorption for EUV, conventional refractive optical systems utilizing light transmission cannot be used; consequently, the optical components of the exposure machine are mirrors rather than lenses. The photomask also changes from a conventional transmission type to a reflection type EUV photomask. Because the incident and reflected light on the EUV photomask cannot be designed to be coaxial, conventional EUV lithography employs a method in which the optical axis is tilted 6° from the vertical direction of the EUV photomask to incident EUV light, and the reflected light, reflected at a minus 6° angle, is irradiated onto the semiconductor substrate. However, due to the tilting of the optical axis, the EUV light incident on the EUV photomask creates a shadow of the EUV photomask pattern (absorption layer pattern), which leads to a problem of degraded transfer performance. Subsequently, improving transfer performance becomes a challenge in order to achieve further miniaturization.

[0004] In current EUV photomasks, a film composed mainly of tantalum (Ta) with a film thickness of 60 to 90 nm is used as the light absorption layer. When exposure for pattern transfer is performed in this EUV photomask, depending on the relationship between the incident direction and the direction of the mask pattern, there is a risk of causing a decrease in contrast at the edge portion that becomes the shadow of the mask pattern. Consequently, problems such as an increase in line edge roughness of the transfer pattern on the semiconductor substrate or inability to form the line width to the target dimensions occur, and transfer performance deteriorates.

[0005] Regarding this problem, methods have been proposed to suppress EUV reflectance by using a material with a high decay coefficient k in the absorption layer [e.g., see Patent Document 1] or by using a phase shift effect [e.g., see Patent Document 2].

[0006] In a reflective phase shift mask, the reflected light that passes through the absorption layer and is sensitized has a phase difference with the light reflected from the aperture. Similar to a transmissive phase shift mask, this reflective phase shift mask can improve optical contrast on the wafer and enhance the resolution of the transfer pattern by utilizing a phase shift effect.

[0007] For example, the reflective mask using a phase shift effect described in Patent Document 2 has an optimal phase difference value of 170 to 190 degrees. This is a value including 180 degrees, which is the optimal phase difference value of a conventional transmissive phase shift mask.

[0008] However, in the case of a reflective mask, since EUV light is incident at an angle, some of the reflected light passes through the edge portion of the absorption layer pattern. Because the reflected light reaching the edge portion is out of phase with the reflected light at the center of the pattern, the optimal phase difference of the absorption layer is different by 180 degrees. That is, the inventors have discovered that the optimal phase difference of the absorption layer in a reflective mask is a value different from the "180 degrees" used in conventional design concepts.

[0009] As such, in the reflective phase shift mask of the prior art, the phase shift effect could not be fully utilized, and its transferability (especially resolution) was insufficient. Prior art literature

[0010] International Publication No. 2018 / 159785 Japanese Patent No. 6287099 The problem to be solved

[0011] The present disclosure aims to provide a reflective photomask blank and a reflective photomask having high transferability (particularly resolution) and maximizing the use of phase shift effects. means of solving the problem

[0012] The present invention is made to solve the above problem, and a reflective photomask blank according to one embodiment of the present invention comprises a substrate, a reflective layer that reflects EUV light having a multilayer film structure formed on the substrate, a protective layer formed on the reflective layer and protecting the reflective layer, and an absorbing layer that absorbs EUV light formed on the protective layer, wherein the absorbing layer has a phase difference within a range of 200 degrees or more and 280 degrees or less.

[0013] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may have a phase difference within the range of 215 degrees or more and 270 degrees or less.

[0014] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may have a phase difference within a range of 230 degrees or more and 260 degrees or less.

[0015] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may have a refractive index n for EUV light that is less than 0.93.

[0016] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may have a refractive index n for EUV light that is less than 0.92.

[0017] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may be composed of a material containing at least one of the elements Ru, Rh, Mo, Pd, Ag, Pt, Au, Os, Ir, and Re.

[0018] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may have a reflectance of EUV light within a range of 2% or more and 20% or less.

[0019] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may be composed of a material containing at least one of the elements Pt, Au, Ir, and Re.

[0020] In addition, the absorption layer in the reflective photomask blank according to one embodiment of the present invention may be composed of a material containing at least one of the elements Mo, W, Nb, Hg, Fe, Ta, V, Bi, Ti, Zr, Hf, C, B, Be, and Al.

[0021] A reflective photomask according to one embodiment of the present invention comprises a substrate, a reflective layer having a multilayer film structure formed on the substrate that reflects EUV light, a protective layer formed on the reflective layer that protects the reflective layer, and an absorption pattern layer formed on the protective layer that absorbs EUV light having a pattern formed thereon, wherein the absorption pattern layer has a phase difference within a range of 200 degrees or more and 280 degrees or less.

[0022] In addition, the absorption pattern layer in the reflective photomask according to one embodiment of the present invention may have a phase difference within a range of 215 degrees or more and 270 degrees or less.

[0023] In addition, the absorption pattern layer in the reflective photomask according to one embodiment of the present invention may have a phase difference within a range of 230 degrees or more and 260 degrees or less.

[0024] In addition, in the reflective photomask according to one embodiment of the present invention, the absorption pattern layer may have a refractive index n for EUV light that is less than 0.93.

[0025] In addition, in the reflective photomask according to one embodiment of the present invention, the absorption pattern layer may have a refractive index n for EUV light that is less than 0.92.

[0026] In addition, the absorption pattern layer in the reflective photomask according to one embodiment of the present invention may be composed of a material containing at least one of the elements Ru, Rh, Mo, Pd, Ag, Pt, Au, Os, Ir, and Re.

[0027] In addition, the absorption pattern layer in the reflective photomask according to one embodiment of the present invention may have a reflectance of EUV light within a range of 2% or more and 20% or less.

[0028] In addition, the absorption pattern layer in the reflective photomask according to one embodiment of the present invention may be composed of a material containing at least one of the elements Pt, Au, Ir, and Re.

[0029] In addition, the absorption pattern layer in the reflective photomask according to one embodiment of the present invention may be composed of a material containing at least one of the elements Mo, W, Nb, Hg, Fe, Ta, V, Bi, Ti, Zr, Hf, C, B, Be, and Al. Effects of the invention

[0030] With a reflective photomask blank and a reflective photomask according to one embodiment of the present disclosure, a sufficient phase shift effect is obtained, and it is possible to improve wafer transfer performance (especially resolution). Brief explanation of the drawing

[0031] FIG. 1 is a cross-sectional view illustrating the structure of a reflective photomask blank according to the present embodiment. FIG. 2 is a cross-sectional view illustrating the structure of a reflective photomask according to the present embodiment. Figure 3 is a graph showing the optical constants of each metal material at the wavelength of EUV light. FIG. 4 is a schematic cross-sectional view illustrating the structure of a reflective photomask blank according to an embodiment of the present invention. FIG. 5 is a schematic cross-sectional view illustrating the manufacturing process of a reflective photomask according to an embodiment of the present invention. FIG. 6 is a schematic cross-sectional view illustrating the manufacturing process of a reflective photomask according to an embodiment of the present invention. FIG. 7 is a schematic cross-sectional view illustrating the manufacturing process of a reflective photomask according to an embodiment of the present invention. FIG. 8 is a schematic cross-sectional view illustrating the structure of a reflective photomask according to an embodiment of the present invention. FIG. 9 is a graph showing NILS of a reflective photomask according to an embodiment of the present invention. FIG. 10 is a graph showing the phase difference of a reflective photomask according to an embodiment of the present invention. Specific details for implementing the invention

[0032] One embodiment of the present disclosure will be described with reference to the drawings.

[0033] Herein, the configurations shown in the drawings are schematic, and the relationship between thickness and planar dimensions, the ratio of the thickness of each layer, etc., differ from reality. Furthermore, the embodiments described below are examples of configurations for embodying the technical concept of the present disclosure, and the technical concept of the present disclosure is not limited to the materials, shapes, structures, etc. of the constituent parts. Various modifications may be added to the technical concept of the present disclosure within the technical scope defined by the claims described in the patent claims.

[0034] (Composition of reflective photomask blank and reflective photomask)

[0035] FIG. 1 is a schematic cross-sectional view illustrating a reflective photomask blank (100) according to an embodiment of the present invention. As shown in FIG. 1, the reflective photomask blank (100) according to an embodiment of the present invention comprises a substrate (11), a reflective layer (12) formed on the substrate (11), a protective layer (13) formed on the reflective layer (12), and an absorption layer (14) formed on the protective layer (13). FIG. 2 is a schematic cross-sectional view illustrating a reflective photomask (200) according to an embodiment of the present invention. Here, the reflective photomask (200) according to an embodiment of the present invention illustrated in FIG. 2 is formed by patterning the absorption layer (14) of the reflective photomask blank (100) according to an embodiment of the present invention illustrated in FIG. 1. Each layer will be described in detail below.

[0036] (Circuit board)

[0037] For the substrate (11) according to an embodiment of the present invention, for example, a flat Si substrate or a synthetic quartz substrate may be used. In addition, for the substrate (11), low thermal expansion glass with added titanium may be used, but the present embodiment is not limited to these materials as long as they have a low coefficient of thermal expansion.

[0038] In addition, as shown in FIG. 4 described later, a back conductive film (15) can be formed on the surface of the substrate (11) where the reflective layer (12) is not formed. The back conductive film (15) is a film for fixing the reflective photomask (200) using the principle of an electrostatic chuck when installing it in an exposure machine.

[0039] (Reflective layer)

[0040] The reflective layer (12) according to an embodiment of the present invention may be a multilayer reflective film (i.e., an EUV light reflective film having a multilayer structure) made of a combination of materials with significantly different refractive indices for EUV light. The reflective layer (12) including the multilayer reflective film may be formed by stacking layers of a combination such as Mo (molybdenum) and Si (silicon) or Mo (molybdenum) and Be (beryllium) repeatedly for about 40 cycles.

[0041] (Protection layer)

[0042] The protective layer (13) according to an embodiment of the present invention is a layer that functions as an etching stopper to prevent damage to the reflective layer (12) when the absorption pattern layer (14a) is formed by etching. Additionally, depending on the material of the reflective layer (12) or the etching conditions, the protective layer (13) may not be present. The protective layer (13) is formed of a material that is resistant to dry etching performed during the pattern formation of the absorption layer (14). For example, the material of the protective layer (13) may be ruthenium (Ru).

[0043] (Absorption layer and absorption pattern layer)

[0044] As illustrated in FIG. 1, the absorption layer (14) is a layer formed on the protective layer (13) and is a layer that absorbs EUV light, which is an exposure light. Additionally, the absorption layer (14) is a layer that forms an absorption pattern layer (transfer pattern) (14a), which is a fine pattern for transfer. That is, by removing a part of the absorption layer (14) of the reflective photomask blank (100), that is, by patterning the absorption layer (14), the absorption pattern (absorption pattern layer (14a)) of the reflective photomask (200) illustrated in FIG. 2 is formed.

[0045] In the portion where the absorption layer (14) (absorption pattern layer (14a)) is formed, EUV light is absorbed and some of the light is reflected. Meanwhile, in the opening of the pattern (the portion without the absorption layer (14)), EUV light is reflected from the reflection layer (12) through the protective layer (13). The reflected light from the portion where the absorption layer (14) is formed forms a desired phase difference with the reflected light from the opening.

[0046] Generally, the reflectance of the absorption layer (14) and the phase difference with the aperture resulting from the patterning are uniquely determined when the optical constants (refractive index n, decay coefficient k) of each layer of the reflective photomask blank and the reflective photomask, the film thickness, and the wavelength of the light used are determined, and can be calculated by optical theory (in detail, for example, see Applied Physical Engineering 3, Sadafumi Yoshida “Thin Film,” Baihukan, 1990). That is, the “phase difference” in this embodiment refers to the difference between the phase of the reflected light of the absorption layer (14) and the phase of the reflected light (at the aperture) of the reflection layer (12).

[0047] In addition, in this embodiment, the respective values ​​of the refractive index n and the decay coefficient k used in calculating the reflectance and the phase difference were actual values ​​using EUV light.

[0048] The NILS (logarithmic slope in normalized space) of the wafer pattern when the wafer is transferred using a reflective photomask (200) depends on the phase difference of the reflective photomask (200). FIG. 9 is a graph showing the NILS (logarithmic slope in normalized space) obtained at four levels of film thickness: 38 nm, 41 nm, 47 nm, and 54 nm, when the absorption layer (14) (absorption pattern layer (14a)) is a monolayer film using a mixed material of rhodium (Rh) and aluminum (Al), and a 19 nm hole pattern on the wafer is exposed under exposure conditions of a numerical aperture (NA) of 0.33. Since Rh has a refractive index n=0.875 and a decay coefficient k=0.03, and Al has a refractive index n=1.03 and a decay coefficient k=0.03, when the composition of RhAl is changed, the refractive index is 0.875 <n<1.03의 범위 내에서 변화하고, 소쇠 계수는 약 k=0.03으로 일정하다. 또한, 동일한 막 두께로 비교한 경우, RhAl의 조성을 바꾸었을 때, 즉 굴절률 n을 바꾸었을 때, 위상차가 변화한다. 또한, 도 9에서는, 횡축에 위상차를 취하고, NILS의 관계를 나타내고 있다.

[0049] NILS (logarithmic gradient in standardized space) is,

[0050] NILS=w×dln(I) / dx … Equation (1)

[0051] It is a contrast value obtained by [method] and serves as an indicator of the resolution of the wafer pattern when the wafer pattern is formed using a reflective photomask (200). Here, “w” represents the line width, and “I” represents the intensity of the energy latent image. In addition, the larger the NILS value, the higher the resolution of the transfer pattern.

[0052] As shown in Fig. 9, there is a relationship between the phase difference and NILS, and NILS becomes maximum when the phase difference is around 230 to 260 degrees.

[0053] In addition, as shown in FIG. 9, the NILS value is 2.49 when the film thickness is 54 nm and the phase difference of the absorption pattern layer (14a) formed of RhAl is 180 degrees.

[0054] In contrast, the NILS value when the phase difference is 200 degrees is 2.60, and the NILS value when the phase difference is 280 degrees is 2.60, and in both cases, the value is about 5% higher than when the phase difference is 180 degrees.

[0055] In addition, the NILS value when the phase difference is 215 degrees is 2.68, and the NILS value when the phase difference is 270 degrees is 2.67, and in both cases, the value is about 7% higher than when the phase difference is 180 degrees.

[0056] In addition, the NILS value when the phase difference is 230 degrees is 2.72, and the NILS value when the phase difference is 260 degrees is 2.71, and in both cases, the value is about 9% higher than when the phase difference is 180 degrees.

[0057] In addition, NILS is maximized when the phase difference is 240 degrees, and the value is 2.74, which is about 10% higher than when the phase difference is 180 degrees.

[0058] As such, compared to the case where the phase difference is 180 degrees, NILS is improved by more than 5% when the phase difference is within the range of 200 degrees or more and 280 degrees or less, by more than 7% when the phase difference is within the range of 215 degrees or more and 270 degrees or less, and by more than 9% when the phase difference is within the range of 230 degrees or more and 260 degrees or less.

[0059] In addition, as shown in FIG. 9, when the film thickness of the absorption pattern layer (14a) is 47 nm and the phase difference is 240 degrees, the NILS value is 2.76, and the value is about 12% higher than when the phase difference is 180 degrees.

[0060] In addition, as shown in FIG. 9, when the film thickness of the absorption pattern layer (14a) is 41 nm and the phase difference is 240 degrees, the NILS value is 2.78, and the value is about 13% higher than when the phase difference is 180 degrees.

[0061] In addition, as shown in FIG. 9, when the film thickness of the absorption pattern layer (14a) is 38 nm and the phase difference is 240 degrees, the NILS value is 2.71, and the value is about 31% higher than when the phase difference is 180 degrees.

[0062] In this regard, it can be seen that in order to improve resolution, the phase difference of the absorption layer (14) is preferably within the range of 200 degrees or more and 280 degrees or less, more preferably within the range of 215 degrees or more and 270 degrees or less, and most preferably within the range of 230 degrees or more and 260 degrees or less.

[0063] In EUV lithography, EUV light is incident obliquely and reflected from the reflection layer (12), but the transfer performance onto the wafer (semiconductor substrate) may deteriorate due to the projection effect in which the absorption layer (14) (absorption pattern layer (14a)) obstructs the light path. It is known that this deterioration in transfer performance can be reduced by making the thickness of the absorption layer (14) that absorbs EUV light thin.

[0064] It is preferable that the film thickness of the absorption layer (14) be 60 nm or less. When the film thickness of the absorption layer (14) is 60 nm or less, the projection effect can be sufficiently reduced and the transfer performance improved compared to a conventional Ta-based absorption film.

[0065] FIG. 10 is a graph showing the relationship between the film thickness and the phase difference of the absorption layer (14) calculated in a simulation when the refractive index n of the absorption layer (14) for EUV light is 0.90, 0.91, 0.92, 0.93, and 0.94.

[0066] As illustrated in FIG. 10, the smaller the refractive index n of the absorption layer (14) for EUV light, the thinner the film thickness can be to obtain a desired phase difference. When the refractive index n of the absorption layer (14) for EUV light is 0.93, the minimum film thickness to obtain a phase difference of 230 to 260 degrees is 60 nm, which is approximately the same as the film thickness of a conventional Ta-based absorption film. Therefore, it is preferable that the refractive index n of the absorption layer (14) for EUV light is less than 0.93, as this allows the film thickness to be thinner than 60 nm. Furthermore, it is even more preferable that the refractive index n of the absorption layer (14) for EUV light is less than 0.92, as this allows the minimum film thickness to obtain a phase difference of 230 to 260 degrees to be 50 nm or less.

[0067] Figure 3 is a graph showing the optical constants for each metal material at a wavelength of 13.5 nm of EUV light. The horizontal axis of the graph in Figure 3 represents the refractive index n, and the vertical axis represents the decay coefficient k. From Figure 3, it can be seen that since the refractive index n of Ru, Rh, Mo, Pd, Ag, Pt, Au, Os, Ir, and Re is less than 0.93, the projection effect can be reduced by using these material groups. Furthermore, the aforementioned "Ru, Rh, Mo, Pd, Ag, Pt, Au, Os, Ir, Re" will be defined below for convenience as the "first material group."

[0068] The material of the absorption layer (14) may be a mixture if it contains elements of the first material group. If it is a mixture, the optical constants (refractive index n, decay coefficient k) of the absorption layer (14) can be controlled by changing the composition, and the desired phase difference and reflectance can be obtained. That is, it is preferable that the absorption layer (14) be composed of a material containing at least one of the elements Ru, Rh, Mo, Pd, Ag, Pt, Au, Os, Ir, and Re.

[0069] The material of the absorption layer (14) may include, in addition to the first group of materials described above, at least one of tin (Sn), indium (In), tantalum (Ta), aluminum (Al), niobium (Nb), and titanium (Ti). If it is an oxide, nitride, or oxynitride of Sn, In, or Ta, further improvement in heat resistance and improved processability with existing etching devices can be expected because it has a high melting point. In addition, if it is Al, Nb, or Ti, further improvement in cleaning resistance due to the formation of a passivation film can be expected.

[0070] Here, if the aforementioned “Sn, In, Ta, Al, Nb, Ti” is defined for convenience as the “second material group,” the absorption layer (14) may be composed only of elements of the first material group, or may be composed of elements of the first material group and elements of the second material group. Additionally, the absorption layer (14) may be composed of elements of the first material group and elements other than those of the second material group, or may be composed of elements of the first material group, elements of the second material group, and elements other than those of the second material group. Furthermore, when the absorption layer (14) is composed of elements of the first material group and elements of the second material group, it is preferable that the content of the elements of the first material group be 70 atomic percent or more of the total elements of the absorption layer (14), more preferable that it be 80 atomic percent or more, and even more preferable that it be 90 atomic percent or more.

[0071] The material of the absorption layer (14) is preferably composed of a material containing at least one of the elements Pt, Au, Ir, and Re. Pt, Au, Ir, and Re are materials that can be expected to improve processability with conventional etching devices among the first group of materials described above, and are also materials with high resistance to hydrogen radicals that can be used when cleaning EUV exposure devices. In addition, since the refractive index n is less than 0.92, a reduction in projection effect can be expected. In addition, the aforementioned “Pt, Au, Ir, Re” are hereinafter defined as the “third group of materials” for convenience.

[0072] The material of the absorption layer (14) may include at least one of Mo, W, Nb, Hg, Fe, Ta, V, Bi, Ti, Zr, Hf, C, B, Be, and Al in addition to the third material group described above. Here, "Mo, W, Nb, Hg, Fe, Ta, V, Bi, Ti, Zr, Hf, C, B, Be, Al" is defined as the "fourth material group." If the fourth material group is included, improved processability with existing etching devices and improved resistance to hydrogen radicals can be expected.

[0073] The absorption layer (14) may be composed only of elements of the third material group, or may be composed of elements of the third material group and elements of the fourth material group. Additionally, the absorption layer (14) may be composed of elements of the third material group and elements other than those of the fourth material group, or may be composed of elements of the third material group, elements of the fourth material group, and elements other than those of the fourth material group. Furthermore, when the absorption layer (14) is composed of elements of the third material group and elements of the fourth material group, it is preferable that the content of the elements of the third material group be 20 atomic percent or more of the total elements of the absorption layer (14).

[0074] In order to obtain a sufficient phase shift effect, the reflectance of the absorption layer (14) is preferably 1% or more and 30% or less in absolute reflectance, and more preferably 2% or more and 20% or less. Here, "absolute reflectance" refers to a value calculated as the ratio of the amount of light reflected from the actual sample to the amount of light directly measured from the light source. That is, it refers to the reflectance when the intensity of the incident light is set to 100%. Furthermore, the term "absolute reflectance" is used in this embodiment to distinguish it from "relative reflectance," which refers to the ratio of the reflectance of the multilayer reflectance layer (reflectance layer (12)) (approx. 66%) to the reflectance of the absorption layer (14). As such, "absolute reflectance" in this embodiment is a different concept from "relative reflectance."

[0075] In addition, a hard mask layer may be provided on the absorption layer (14). For the hard mask layer, a material resistant to dry etching, such as a Cr-based film or a Si-based film, is used.

[0076] [Example]

[0077] The present disclosure will be explained in more detail below by way of examples, but the present disclosure is not limited in any way by the examples.

[0078] <Example 1>

[0079] As the substrate shown in Fig. 4, a synthetic quartz substrate having low thermal expansion was used. On the substrate, 40 stacked films of silicon (Si) and molybdenum (Mo) were formed as a multilayer reflective film. The film thickness of the multilayer reflective film was set to 280 nm.

[0080] Next, a capping layer (protective layer) was formed on the multilayer reflective film using ruthenium (Ru) to have a film thickness of 3.5 nm. As a result, a reflective portion having a multilayer reflective film and a capping layer was formed on the substrate.

[0081] An absorption layer containing rhodium (Rh) and aluminum (Al) was deposited on the capping layer to a thickness of 47 nm. The ratio of the number of atoms of rhodium (Rh) and aluminum (Al) in the absorption layer was measured by XPS (X-ray photoelectron spectroscopy) and was 66:34. In addition, the crystallinity of the absorption layer was measured by XRD (X-ray diffraction) and it was found that it was amorphous, although it showed some crystallinity.

[0082] Next, on the side of the substrate where the multilayer reflective film was not formed, a back-side conductive film was formed using chromium nitride (CrN) to a thickness of 100 nm. A reflective photomask blank (100) was fabricated.

[0083] A multi-stage sputtering device was used to deposit each film on the substrate. The thickness of each film was controlled by the sputtering time.

[0084] Next, a method for manufacturing a reflective photomask (200) is described using FIGS. 5 to 8. As shown in FIG. 5, a positive type chemical amplification resist (SEBP9012: manufactured by Shin-Etsu Chemical Co., Ltd.) is applied by spin coating to a film thickness of 120 nm on the absorption layer (14) of a reflective photomask blank (100), baked at 110°C for 10 minutes, and a resist film (16) is formed.

[0085] Next, a predetermined pattern was drawn on the resist film (16) by an electron beam illustrator (JBX3030: manufactured by Nihon Denshi Co., Ltd.).

[0086] After that, a pre-baking treatment was performed at 110°C for 10 minutes, followed by a developing treatment using a spray developer (SFG3000: manufactured by Sigma Mertec). By doing so, a resist pattern (16a) was formed as shown in FIG. 6.

[0087] Next, using the resist pattern (16a) as an etching mask, the patterning of the absorption layer (14) was performed by dry etching using a chlorine-based gas. As a result, as shown in FIG. 7, an absorption pattern (absorption pattern layer) (14a) was formed on the absorption layer (14).

[0088] Next, the resist pattern (16a) was peeled off to produce a reflective photomask (200) according to the present embodiment as shown in FIG. 8.

[0089] In this embodiment, the absorption pattern (14a) formed on the absorption layer (14) was made into a 76 nm hole pattern on a reflective photomask (200) for transfer evaluation.

[0090] For Example 1 formed as described above, the refractive index and decay coefficient of the absorption layer were measured (actually measured) using EUV light with a wavelength of 13.5 nm. As a result, the refractive index n and decay coefficient k of the absorption layer of Example 1 were n=0.924 and k=0.03, respectively.

[0091] In addition, for each subsequent example and each comparative example, the refractive index and decay coefficient of the absorption layer were measured (actually measured) using EUV light with a wavelength of 13.5 nm, just as in the case of Example 1.

[0092] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.4%, and the phase difference was 205 degrees.

[0093] <Example 2>

[0094] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=70:30, and a film was formed with a thickness of 47 nm. Except for that, the reflective photomask of Example 2 was fabricated in the same manner as in Example 1.

[0095] The refractive index n and decay coefficient k of the absorption layer of Example 2 formed as described above at a wavelength of 13.5 nm were n=0.919 and k=0.03, respectively.

[0096] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.7%, and the phase difference was 220 degrees.

[0097] <Example 3>

[0098] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=75:25, and a film was formed with a thickness of 47 nm. Except for that, the reflective photomask of Example 3 was fabricated in the same manner as in Example 1.

[0099] The refractive index n and decay coefficient k of the absorption layer of Example 3 formed as described above at a wavelength of 13.5 nm were n=0.912 and k=0.03, respectively.

[0100] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 4.3%, and the phase difference was 240 degrees.

[0101] <Example 4>

[0102] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=82:18, and a film was formed with a thickness of 47 nm. Except for that, the reflective photomask of Example 4 was fabricated in the same manner as in Example 1.

[0103] The refractive index n and decay coefficient k of the absorption layer of Example 4 formed as described above at a wavelength of 13.5 nm were n=0.902 and k=0.03, respectively.

[0104] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 5.3%, and the phase difference was 265 degrees.

[0105] <Example 5>

[0106] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=86:14, and a film was formed with a thickness of 47 nm. Except for that, the reflective photomask of Example 5 was fabricated in the same manner as in Example 1.

[0107] The refractive index n and decay coefficient k of the absorption layer of Example 5 formed as described above at a wavelength of 13.5 nm were n=0.896 and k=0.03, respectively.

[0108] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 5.9%, and the phase difference was 275 degrees.

[0109] <Example 6>

[0110] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=67:33, and a film was formed with a thickness of 54 nm. Except for that, the reflective photomask of Example 6 was fabricated in the same manner as in Example 1.

[0111] The refractive index n and decay coefficient k of the absorption layer of Example 6 formed as described above at a wavelength of 13.5 nm were n=0.923 and k=0.03, respectively.

[0112] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.6%, and the phase difference was 240 degrees.

[0113] <Example 7>

[0114] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=84:16, and a film was formed with a thickness of 41 nm. Except for that, the reflective photomask of Example 7 was fabricated in the same manner as in Example 1.

[0115] The refractive index n and decay coefficient k of the absorption layer of Example 7 formed as described above at a wavelength of 13.5 nm were n=0.899 and k=0.03, respectively.

[0116] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 4.4%, and the phase difference was 240 degrees.

[0117] <Example 8>

[0118] The composition of RhAl, the material of the absorption layer, was changed so that the atomic number ratio was Rh:Al=98:2, and a film was formed with a thickness of 38 nm. Except for that, the reflective photomask of Example 8 was fabricated in the same manner as in Example 1.

[0119] The refractive index n and decay coefficient k of the absorption layer of Example 8 formed as described above at a wavelength of 13.5 nm were n=0.878 and k=0.03, respectively.

[0120] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 9.2%, and the phase difference was 240 degrees.

[0121] <Example 9>

[0122] The material of the absorption layer was changed to rhodium (Rh), and a film was formed with a thickness of 33 nm. Except for that, the reflective photomask of Example 9 was fabricated in the same manner as in Example 1.

[0123] The refractive index n and decay coefficient k of the absorption layer of Example 9 formed as described above at a wavelength of 13.5 nm were n=0.875 and k=0.03, respectively.

[0124] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 11.0%, and the phase difference was 240 degrees.

[0125] <Example 10>

[0126] The material of the absorption layer was changed to a mixed material (RuNb) in which ruthenium (Ru) and niobium (Nb) are homogeneous with an atomic number ratio of 85:15, and a film was formed to a thickness of 44 nm. Except for that, the reflective photomask of Example 10 was fabricated in the same manner as in Example 1.

[0127] The refractive index n and decay coefficient k of the absorption layer of Example 10 formed as described above at a wavelength of 13.5 nm were n=0.895 and k=0.015, respectively.

[0128] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 17.0%, and the phase difference was 240 degrees.

[0129] <Example 11>

[0130] The material of the absorption layer was changed to a mixed material (RuAl) in which ruthenium (Ru) and aluminum (Al) are homogeneous with an atomic number ratio of 59:41, and a film was formed to a thickness of 72 nm. Except for that, the reflective photomask of Example 11 was fabricated in the same manner as in Example 1.

[0131] The refractive index n and decay coefficient k of the absorption layer of Example 11 formed as described above at a wavelength of 13.5 nm were n=0.940 and k=0.023, respectively.

[0132] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.7%, and the phase difference was 240 degrees.

[0133] <Example 12>

[0134] The material of the absorption layer was changed to a mixed material (SnRuO) in which tin oxide (SnO) and ruthenium (Ru) are homogeneous with an atomic ratio of 20:80, and a film was deposited to a thickness of 42 nm. Except for that, the reflective photomask of Example 12 was fabricated in the same manner as in Example 1.

[0135] The refractive index n and decay coefficient k of the absorption layer of Example 12 formed as described above at a wavelength of 13.5 nm were n=0.896 and k=0.03, respectively.

[0136] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.1%, and the phase difference was 240 degrees.

[0137] <Example 13>

[0138] The thickness of the SnRuO film of the absorption layer was changed to 39 nm and the film was deposited. Except for that, the reflective photomask of Example 13 was prepared in the same manner as in Example 12.

[0139] The refractive index n and decay coefficient k of the absorption layer of Example 13 formed as described above at a wavelength of 13.5 nm were n=0.896 and k=0.03, respectively.

[0140] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 8.9%, and the phase difference was 225 degrees.

[0141] <Example 14>

[0142] The material of the absorption layer was changed to a mixed material (InRuO) in which indium oxide (InO) and ruthenium (Ru) are homogeneous with an atomic ratio of 15:85, and a film was deposited to a thickness of 42 nm. Except for that, the reflective photomask of Example 14 was fabricated in the same manner as in Example 1.

[0143] The refractive index n and decay coefficient k of the absorption layer of Example 14 formed as described above at a wavelength of 13.5 nm were n=0.895 and k=0.03, respectively.

[0144] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.3%, and the phase difference was 240 degrees.

[0145] <Example 15>

[0146] The thickness of the InRuO film of the absorption layer was changed to 39 nm and the film was deposited. Except for that, the reflective photomask of Example 15 was prepared in the same manner as in Example 14.

[0147] The refractive index n and decay coefficient k of the absorption layer of Example 15 formed as described above at a wavelength of 13.5 nm were n=0.895 and k=0.03, respectively.

[0148] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 9.3%, and the phase difference was 225 degrees.

[0149] <Example 16>

[0150] The material of the absorption layer was changed to a mixed material (TaTi) in which tantalum (Ta) and titanium (Ti) are homogeneously mixed in an atomic ratio of 60:40, and a film was deposited to a thickness of 78 nm. Except for that, the reflective photomask of Example 16 was fabricated in the same manner as in Example 1.

[0151] The refractive index n and decay coefficient k of the absorption layer of Example 16 formed as described above at a wavelength of 13.5 nm were n=0.947 and k=0.030, respectively.

[0152] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 1.2%, and the phase difference was 212 degrees.

[0153] <Example 17>

[0154] The material of the absorption layer was changed to titanium (Ti), and a film was formed with a thickness of 80 nm. Except for that, the reflective photomask of Example 17 was fabricated in the same manner as in Example 1.

[0155] The refractive index n and decay coefficient k of the absorption layer of Example 17 formed as described above at a wavelength of 13.5 nm were n=0.952 and k=0.014, respectively.

[0156] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 6.5%, and the phase difference was 212 degrees.

[0157] <Example 18>

[0158] The material of the absorption layer was changed to a mixed material (MoPd) in which molybdenum (Mo) and palladium (Pd) are homogeneous with an atomic ratio of 40:60, and a film was deposited to a thickness of 45 nm. Except for that, the reflective photomask of Example 18 was fabricated in the same manner as in Example 1.

[0159] The refractive index n and decay coefficient k of the absorption layer of Example 18 formed as described above at a wavelength of 13.5 nm were n=0.896 and k=0.03, respectively.

[0160] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 6.6%, and the phase difference was 235 degrees.

[0161] <Example 19>

[0162] The material of the absorption layer was changed to platinum (Pt), and a film was formed with a thickness of 45 nm. Except for that, the reflective photomask of Example 19 was fabricated in the same manner as in Example 1.

[0163] The refractive index n and decay coefficient k of the absorption layer of Example 19 formed as described above at a wavelength of 13.5 nm were n=0.890 and k=0.06, respectively.

[0164] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 1.3%, and the phase difference was 243 degrees.

[0165] <Example 20>

[0166] The material of the absorption layer was changed to a mixed material (IrPt) in which iridium (Ir) and platinum (Pt) are homogeneous with an atomic ratio of 75:25, and a film was formed to a thickness of 45 nm. Except for that, the reflective photomask of Example 20 was fabricated in the same manner as in Example 1.

[0167] The refractive index n and decay coefficient k of the absorption layer of Example 20 formed as described above at a wavelength of 13.5 nm were n=0.902 and k=0.049, respectively.

[0168] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 234 degrees.

[0169] <Example 21>

[0170] The material of the absorption layer was changed to a mixed material (IrAu) in which iridium (Ir) and gold (Au) are homogeneous with an atomic ratio of 40:60, and a film was deposited to a thickness of 45 nm. Except for that, the reflective photomask of Example 21 was fabricated in the same manner as in Example 1.

[0171] The refractive index n and decay coefficient k of the absorption layer of Example 21 formed as described above at a wavelength of 13.5 nm were n=0.901 and k=0.049, respectively.

[0172] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 234 degrees.

[0173] <Example 22>

[0174] The material of the absorption layer was changed to a mixed material (RePt) in which rhenium (Re) and platinum (Pt) are homogeneous with an atomic ratio of 75:25, and a film was formed to a thickness of 46 nm. Except for that, the reflective photomask of Example 22 was fabricated in the same manner as in Example 1.

[0175] The refractive index n and decay coefficient k of the absorption layer of Example 22 formed as described above at a wavelength of 13.5 nm were n=0.909 and k=0.045, respectively.

[0176] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 240 degrees.

[0177] <Example 23>

[0178] The material of the absorption layer was changed to a mixed material (ReAu) in which rhenium (Re) and gold (Au) are homogeneous with an atomic ratio of 40:60, and a film was formed to a thickness of 45 nm. Except for that, the reflective photomask of Example 23 was fabricated in the same manner as in Example 1.

[0179] The refractive index n and decay coefficient k of the absorption layer of Example 23 formed as described above at a wavelength of 13.5 nm were n=0.905 and k=0.047, respectively.

[0180] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.8%, and the phase difference was 227 degrees.

[0181] <Example 24>

[0182] The material of the absorption layer was changed to a mixed material (PtMo) in which platinum (Pt) and molybdenum (Mo) are homogeneous with an atomic ratio of 20:80, and a film was deposited to a thickness of 48 nm. Except for that, the reflective photomask of Example 24 was fabricated in the same manner as in Example 1.

[0183] The refractive index n and decay coefficient k of the absorption layer of Example 24 formed as described above at a wavelength of 13.5 nm were n=0.918 and k=0.017, respectively.

[0184] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 7.8%, and the phase difference was 213 degrees.

[0185] <Example 25>

[0186] The material of the absorption layer was changed to a mixed material (PtMo) in which platinum (Pt) and molybdenum (Mo) are homogeneous with an atomic ratio of 80:20, and a film was formed to a thickness of 45 nm. Except for that, the reflective photomask of Example 25 was fabricated in the same manner as in Example 1.

[0187] The refractive index n and decay coefficient k of the absorption layer of Example 25 formed as described above at a wavelength of 13.5 nm were n=0.898 and k=0.049, respectively.

[0188] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 234 degrees.

[0189] <Example 26>

[0190] The material of the absorption layer was changed to a mixed material (PtNb) in which platinum (Pt) and niobium (Nb) are homogeneous with an atomic ratio of 35:65, and a film was formed to a thickness of 47 nm. Except for that, the reflective photomask of Example 26 was fabricated in the same manner as in Example 1.

[0191] The refractive index n and decay coefficient k of the absorption layer of Example 26 formed as described above at a wavelength of 13.5 nm were n=0.919 and k=0.024, respectively.

[0192] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 6%, and the phase difference was 214 degrees.

[0193] <Example 27>

[0194] The material of the absorption layer was changed to a mixed material (PtNb) in which platinum (Pt) and niobium (Nb) are homogeneous with an atomic ratio of 80:20, and a film was formed to a thickness of 45 nm. Except for that, the reflective photomask of Example 27 was fabricated in the same manner as in Example 1.

[0195] The refractive index n and decay coefficient k of the absorption layer of Example 27 formed as described above at a wavelength of 13.5 nm were n=0.900 and k=0.049, respectively.

[0196] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 234 degrees.

[0197] <Example 28>

[0198] The material of the absorption layer was changed to a mixed material (AuMo) in which gold (Au) and molybdenum (Mo) are homogeneous with an atomic number ratio of 25:75, and a film was deposited to a thickness of 49 nm. Except for that, the reflective photomask of Example 28 was fabricated in the same manner as in Example 1.

[0199] The refractive index n and decay coefficient k of the absorption layer of Example 28 formed as described above at a wavelength of 13.5 nm were n=0.918 and k=0.018, respectively.

[0200] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 7.6%, and the phase difference was 209 degrees.

[0201] <Example 29>

[0202] The material of the absorption layer was changed to a mixed material (AuMo) in which gold (Au) and molybdenum (Mo) are homogeneous with an atomic ratio of 95:5, and a film was deposited to a thickness of 39 nm. Except for that, the reflective photomask of Example 29 was fabricated in the same manner as in Example 1.

[0203] The refractive index n and decay coefficient k of the absorption layer of Example 29 formed as described above at a wavelength of 13.5 nm were n=0.900 and k=0.050, respectively.

[0204] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.7%, and the phase difference was 228 degrees.

[0205] <Example 30>

[0206] The material of the absorption layer was changed to a mixed material (AuNb) in which gold (Au) and niobium (Nb) are homogeneous with an atomic number ratio of 45:55, and a film was formed to a thickness of 48 nm. Except for that, the reflective photomask of Example 30 was fabricated in the same manner as in Example 1.

[0207] The refractive index n and decay coefficient k of the absorption layer of Example 30 formed as described above at a wavelength of 13.5 nm were n=0.918 and k=0.026, respectively.

[0208] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 4.5%, and the phase difference was 213 degrees.

[0209] <Example 31>

[0210] The material of the absorption layer was changed to a mixed material (AuNb) in which gold (Au) and niobium (Nb) are homogeneous with an atomic ratio of 90:10, and a film was formed to a thickness of 45 nm. Except for that, the reflective photomask of Example 31 was fabricated in the same manner as in Example 1.

[0211] The refractive index n and decay coefficient k of the absorption layer of Example 31 formed as described above at a wavelength of 13.5 nm were n=0.903 and k=0.047, respectively.

[0212] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 234 degrees.

[0213] <Example 32>

[0214] The material of the absorption layer was changed to a mixed material (AuTi) in which gold (Au) and titanium (Ti) are homogeneously mixed in an atomic ratio of 65:35, and a film was deposited to a thickness of 47 nm. Except for that, the reflective photomask of Example 32 was fabricated in the same manner as in Example 1.

[0215] The refractive index n and decay coefficient k of the absorption layer of Example 32 formed as described above at a wavelength of 13.5 nm were n=0.918 and k=0.039, respectively.

[0216] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 1.3%, and the phase difference was 225 degrees.

[0217] <Example 33>

[0218] The material of the absorption layer was changed to a mixed material (AuTi) in which gold (Au) and titanium (Ti) are homogeneously mixed in an atomic ratio of 85:15, and a film was deposited to a thickness of 46 nm. Except for that, the reflective photomask of Example 33 was fabricated in the same manner as in Example 1.

[0219] The refractive index n and decay coefficient k of the absorption layer of Example 33 formed as described above at a wavelength of 13.5 nm were n=0.907 and k=0.046, respectively.

[0220] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 240 degrees.

[0221] <Example 34>

[0222] The material of the absorption layer was changed to a mixed material (AuZr) in which gold (Au) and zirconium (Zr) are homogeneous with an atomic ratio of 70:30, and a film was formed to a thickness of 51 nm. Except for that, the reflective photomask of Example 34 was fabricated in the same manner as in Example 1.

[0223] The refractive index n and decay coefficient k of the absorption layer of Example 34 formed as described above at a wavelength of 13.5 nm were n=0.917 and k=0.038, respectively.

[0224] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.1%, and the phase difference was 218 degrees.

[0225] <Example 35>

[0226] The material of the absorption layer was changed to a mixed material (AuZr) in which gold (Au) and zirconium (Zr) are homogeneous with an atomic ratio of 90:10, and a film was formed to a thickness of 46 nm. Except for that, the reflective photomask of Example 35 was fabricated in the same manner as in Example 1.

[0227] The refractive index n and decay coefficient k of the absorption layer of Example 35 formed as described above at a wavelength of 13.5 nm were n=0.905 and k=0.047, respectively.

[0228] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.5%, and the phase difference was 248 degrees.

[0229] <Example 36>

[0230] The material of the absorption layer was changed to a mixed material (IrMo) in which iridium (Ir) and molybdenum (Mo) are homogeneous with an atomic ratio of 30:70, and a film was deposited to a thickness of 49 nm. Except for that, the reflective photomask of Example 36 was fabricated in the same manner as in Example 1.

[0231] The refractive index n and decay coefficient k of the absorption layer of Example 36 formed as described above at a wavelength of 13.5 nm were n=0.918 and k=0.018, respectively.

[0232] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 7.6%, and the phase difference was 209 degrees.

[0233] <Example 37>

[0234] The material of the absorption layer was changed to a mixed material (IrMo) in which iridium (Ir) and molybdenum (Mo) are homogeneous with an atomic ratio of 90:10, and a film was deposited to a thickness of 45 nm. Except for that, the reflective photomask of Example 37 was fabricated in the same manner as in Example 1.

[0235] The refractive index n and decay coefficient k of the absorption layer of Example 37 formed as described above at a wavelength of 13.5 nm were n=0.907 and k=0.041, respectively.

[0236] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.7%, and the phase difference was 227 degrees.

[0237] <Example 38>

[0238] The material of the absorption layer was changed to a mixed material (IrW) in which iridium (Ir) and tungsten (W) are homogeneous with an atomic ratio of 50:50, and a film was formed to a thickness of 47 nm. Except for that, the reflective photomask of Example 38 was fabricated in the same manner as in Example 1.

[0239] The refractive index n and decay coefficient k of the absorption layer of Example 38 formed as described above at a wavelength of 13.5 nm were n=0.919 and k=0.039, respectively.

[0240] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 1.3%, and the phase difference was 225 degrees.

[0241] <Example 39>

[0242] The material of the absorption layer was changed to a mixed material (IrW) in which iridium (Ir) and tungsten (W) are homogeneous with an atomic ratio of 90:10, and a film was formed to a thickness of 46 nm. Except for that, the reflective photomask of Example 39 was fabricated in the same manner as in Example 1.

[0243] The refractive index n and decay coefficient k of the absorption layer of Example 39 formed as described above at a wavelength of 13.5 nm were n=0.908 and k=0.044, respectively.

[0244] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 240 degrees.

[0245] <Example 40>

[0246] The material of the absorption layer was changed to a mixed material (IrNb) in which iridium (Ir) and niobium (Nb) are homogeneous with an atomic ratio of 50:50, and a film was deposited to a thickness of 47 nm. Except for that, the reflective photomask of Example 40 was fabricated in the same manner as in Example 1.

[0247] The refractive index n and decay coefficient k of the absorption layer of Example 40 formed as described above at a wavelength of 13.5 nm were n=0.920 and k=0.025, respectively.

[0248] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 6%, and the phase difference was 214 degrees.

[0249] <Example 41>

[0250] The material of the absorption layer was changed to a mixed material (IrNb) in which iridium (Ir) and niobium (Nb) are homogeneous with an atomic ratio of 90:10, and the film was deposited to a thickness of 46 nm. Except for that, the reflective photomask of Example 41 was fabricated in the same manner as in Example 1.

[0251] The refractive index n and decay coefficient k of the absorption layer of Example 41 formed as described above at a wavelength of 13.5 nm were n=0.908 and k=0.041, respectively.

[0252] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.1%, and the phase difference was 237 degrees.

[0253] <Example 42>

[0254] The material of the absorption layer was changed to a mixed material (IrTa) in which iridium (Ir) and tantalum (Ta) are homogeneous with an atomic number ratio of 85:15, and a film was deposited to a thickness of 45 nm. Except for that, the reflective photomask of Example 42 was fabricated in the same manner as in Example 1.

[0255] The refractive index n and decay coefficient k of the absorption layer of Example 42 formed as described above at a wavelength of 13.5 nm were n=0.911 and k=0.044, respectively.

[0256] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.8%, and the phase difference was 219 degrees.

[0257] <Example 43>

[0258] The material of the absorption layer was changed to a mixed material (IrTa) in which iridium (Ir) and tantalum (Ta) are homogeneous with an atomic ratio of 95:5, and a film was deposited to a thickness of 46 nm. Except for that, the reflective photomask of Example 43 was fabricated in the same manner as in Example 1.

[0259] The refractive index n and decay coefficient k of the absorption layer of Example 43 formed as described above at a wavelength of 13.5 nm were n=0.907 and k=0.045, respectively.

[0260] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.5%, and the phase difference was 248 degrees.

[0261] <Example 44>

[0262] The material of the absorption layer was changed to a mixed material (IrV) in which iridium (Ir) and vanadium (V) are homogeneous with an atomic ratio of 65:35, and a film was formed to a thickness of 45 nm. Except for that, the reflective photomask of Example 44 was fabricated in the same manner as in Example 1.

[0263] The refractive index n and decay coefficient k of the absorption layer of Example 44 formed as described above at a wavelength of 13.5 nm were n=0.918 and k=0.038, respectively.

[0264] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.4%, and the phase difference was 201 degrees.

[0265] <Example 45>

[0266] The material of the absorption layer was changed to a mixed material (IrV) in which iridium (Ir) and vanadium (V) are homogeneous with an atomic ratio of 90:10, and a film was formed to a thickness of 46 nm. Except for that, the reflective photomask of Example 45 was fabricated in the same manner as in Example 1.

[0267] The refractive index n and decay coefficient k of the absorption layer of Example 45 formed as described above at a wavelength of 13.5 nm were n=0.909 and k=0.043, respectively.

[0268] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.2%, and the phase difference was 240 degrees.

[0269] <Example 46>

[0270] The material of the absorption layer was changed to a mixed material (ReMo) in which rhenium (Re) and molybdenum (Mo) are homogeneous with an atomic ratio of 45:55, and a film was deposited to a thickness of 48 nm. Except for that, the reflective photomask of Example 46 was fabricated in the same manner as in Example 1.

[0271] The refractive index n and decay coefficient k of the absorption layer of Example 46 formed as described above at a wavelength of 13.5 nm were n=0.920 and k=0.021, respectively.

[0272] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 7.8%, and the phase difference was 213 degrees.

[0273] <Example 47>

[0274] The material of the absorption layer was changed to a mixed material (ReMo) in which rhenium (Re) and molybdenum (Mo) are homogeneous with an atomic ratio of 90:10, and a film was formed to a thickness of 47 nm. Except for that, the reflective photomask of Example 47 was fabricated in the same manner as in Example 1.

[0275] The refractive index n and decay coefficient k of the absorption layer of Example 47 formed as described above at a wavelength of 13.5 nm were n=0.916 and k=0.037, respectively.

[0276] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.5%, and the phase difference was 234 degrees.

[0277] <Example 48>

[0278] The material of the absorption layer was changed to a mixed material (ReW) in which rhenium (Re) and tungsten (W) are homogeneous with an atomic ratio of 75:25, and a film was formed to a thickness of 46 nm. Except for that, the reflective photomask of Example 48 was fabricated in the same manner as in Example 1.

[0279] The refractive index n and decay coefficient k of the absorption layer of Example 48 formed as described above at a wavelength of 13.5 nm were n=0.920 and k=0.038, respectively.

[0280] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.4%, and the phase difference was 216 degrees.

[0281] <Example 49>

[0282] The material of the absorption layer was changed to a mixed material (ReW) in which rhenium (Re) and tungsten (W) are homogeneous with an atomic ratio of 95:5, and a film was formed to a thickness of 46 nm. Except for that, the reflective photomask of Example 49 was fabricated in the same manner as in Example 1.

[0283] The refractive index n and decay coefficient k of the absorption layer of Example 49 formed as described above at a wavelength of 13.5 nm were n=0.916 and k=0.040, respectively.

[0284] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.8%, and the phase difference was 227 degrees.

[0285] <Example 50>

[0286] The material of the absorption layer was changed to a mixed material (ReNb) in which rhenium (Re) and niobium (Nb) are homogeneous with an atomic ratio of 75:25, and the film was deposited to a thickness of 48 nm. Except for that, the reflective photomask of Example 50 was fabricated in the same manner as in Example 1.

[0287] The refractive index n and decay coefficient k of the absorption layer of Example 50 formed as described above at a wavelength of 13.5 nm were n=0.920 and k=0.031, respectively.

[0288] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 2.5%, and the phase difference was 213 degrees.

[0289] <Example 51>

[0290] The material of the absorption layer was changed to a mixed material (ReNb) in which rhenium (Re) and niobium (Nb) are homogeneous with an atomic ratio of 90:10, and the film was deposited to a thickness of 46 nm. Except for that, the reflective photomask of Example 51 was fabricated in the same manner as in Example 1.

[0291] The refractive index n and decay coefficient k of the absorption layer of Example 51 formed as described above at a wavelength of 13.5 nm were n=0.917 and k=0.037, respectively.

[0292] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 4%, and the phase difference was 224 degrees.

[0293] <Comparative Example 1>

[0294] In Comparative Example 1, a photomask equipped with a conventional film made of tantalum (Ta) as the main material was used. In Comparative Example 1, an absorption layer was formed using tantalum nitride (TaN) to have a film thickness of 58 nm, and a surface layer was formed using tantalum oxide (TaO) to have a film thickness of 2 nm to produce a reflective photomask. Except for that, the reflective photomask of Comparative Example 1 was produced in the same manner as in Example 1.

[0295] The absolute reflectance of the absorption layer of Comparative Example 1 formed as described above at a wavelength of 13.5 nm was 1.3%, and the phase difference was 160 degrees.

[0296] <Comparative Example 2>

[0297] The material of the absorption layer was changed to a mixed material (RhAl) in which rhodium (Rh) and aluminum (Al) are homogeneous with an atomic ratio of 60:40, and a film was formed to a thickness of 47 nm. Except for that, the reflective photomask of Comparative Example 2 was fabricated in the same manner as in Example 1.

[0298] The refractive index n and decay coefficient k of the absorption layer of Comparative Example 2 formed as described above at a wavelength of 13.5 nm were n=0.932 and k=0.03, respectively.

[0299] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 3.1%, and the phase difference was 180 degrees.

[0300] <Comparative Example 3>

[0301] The composition of RhAl in the absorption layer material was changed so that the atomic number ratio was Rh:Al=89:11, and a film was formed with a thickness of 47 nm. Except for that, the reflective photomask of Comparative Example 3 was prepared in the same manner as in Example 1.

[0302] The refractive index n and decay coefficient k of the absorption layer of Comparative Example 3 formed as described above at a wavelength of 13.5 nm were n=0.892 and k=0.03, respectively.

[0303] In addition, the absolute reflectance of the absorption layer at a wavelength of 13.5 nm was 6.3%, and the phase difference was 285 degrees.

[0304] <Evaluation>

[0305] For the reflective photomasks obtained in the above-described Examples 1 to 51 and Comparative Examples 1 to 3, the transfer performance was evaluated by the following method. The transfer performance was confirmed by wafer exposure evaluation. In addition, the resolution was evaluated by NILS (Normalized Image Log-Slope) values.

[0306] Using an EUV lithography device (NXE3300B: manufactured by ASML), the absorption pattern of the reflective photomask prepared in each example and comparative example was transferred and exposed onto a semiconductor wafer coated with an EUV positive chemical amplification resist. At this time, the exposure amount was adjusted so that the hole pattern was transferred to 19 nm as designed. Afterwards, the transferred resist pattern was observed and the line width measured by an electron beam dimensioning device, the resolution was confirmed, and evaluated in four stages: “◎”, “○”, “△”, and “×”.

[0307] <Evaluation Criteria>

[0308] ◎: When NILS value is greater than 2.73

[0309] ○: If the NILS value is 2.48 or higher and 2.73 or lower

[0310] △: When the NILS value is 2.40 or higher and less than 2.48

[0311] ×: If NILS value is less than 2.40

[0312] The above evaluation results are shown in Table 1.

[0313] In addition, regarding the NILS value, if the evaluation is "○" or higher, it was deemed acceptable as there are no issues with the overall performance.

[0314]

[0315] Table 1 shows the evaluation results of Examples 1 to 51 and Comparative Examples 1 to 3.

[0316] The phase difference of Comparative Example 1, which had a conventional tantalum (Ta)-based absorption layer with a film thickness of 60 nm, was 160 degrees, and the NILS was 2.37. It can be seen that when the phase difference of the absorption pattern layer is 200 degrees or more and 280 degrees or less, as in Examples 1 to 51, the NILS is larger and the resolution is improved compared to Comparative Example 1.

[0317] In addition, compared to Comparative Example 2, which has a phase difference of 180 degrees, and Comparative Example 3, which has a phase difference of 285 degrees, Examples 1 to 51, which have a phase difference of 200 degrees or more and 280 degrees or less, can be seen to have a larger NILS and improved resolution.

[0318] Hereinafter, the results of comparing the NILS of each example and each comparative example using the graphs shown in Table 1 and Figure 9 will be explained in detail.

[0319] As shown in Examples 1 to 5 and Comparative Examples 2 and 3 of FIG. 9 and Table 1, the NILS value of Comparative Example 2, in which the film thickness is 47 nm and the phase difference of the absorption pattern layer (14a) formed of RhAl is 180 degrees, is 2.47. In contrast, the NILS value of Example 1, in which the phase difference is 205 degrees, is 2.66, and the value is about 7% higher compared to the case where the phase difference is 180 degrees (Comparative Example 2).

[0320] In addition, the NILS value of Example 2, with a phase difference of 220 degrees, is 2.73, and compared to the case with a phase difference of 180 degrees (Comparative Example 2), the value is about 10% higher.

[0321] In addition, the NILS value of Example 3, with a phase difference of 240 degrees, is 2.76, and compared to the case with a phase difference of 180 degrees (Comparative Example 2), the value is about 12% higher.

[0322] In addition, the NILS value of Example 4, with a phase difference of 265 degrees, is 2.67, and compared to the case with a phase difference of 180 degrees (Comparative Example 2), the value is about 8% higher.

[0323] In addition, the NILS value of Example 5, with a phase difference of 275 degrees, is 2.56, and compared to the case with a phase difference of 180 degrees (Comparative Example 2), the value is about 4% higher.

[0324] On the other hand, the NILS value of Comparative Example 3, with a phase difference of 285 degrees, is 2.46, which is almost the same value as when the phase difference is 180 degrees (Comparative Example 2).

[0325] In addition, as shown in Example 6 of FIG. 9 and Table 1, when the film thickness of the absorption pattern layer (14a) is 54 nm, the NILS value of Example 6, which has a phase difference of 240 degrees, is 2.74, and the value is about 10% higher than when the phase difference is 180 degrees with the same film thickness.

[0326] In addition, as shown in Example 7 of FIG. 9 and Table 1, when the film thickness of the absorption pattern layer (14a) is 41 nm, the NILS value of Example 7, which has a phase difference of 240 degrees, is 2.78, and the value is about 13% higher than when the phase difference is 180 degrees with the same film thickness.

[0327] In addition, as shown in Example 8 of FIG. 9 and Table 1, when the film thickness of the absorption pattern layer (14a) is 38 nm, the NILS value of Example 8, which has a phase difference of 240 degrees, is 2.71, and the value is about 31% higher than when the phase difference is 180 degrees with the same film thickness.

[0328] In this regard, it can be seen that in order to improve resolution, the phase difference is preferably within the range of 200 degrees or more and 280 degrees or less, more preferably within the range of 215 degrees or more and 270 degrees or less, and most preferably within the range of 230 degrees or more and 260 degrees or less.

[0329] That is, the range of phase difference suitable for the absorption layer in a reflective mask is significantly different from the "range of 170 degrees or more and 190 degrees or less" used in conventional design concepts, and is "range of 200 degrees or more and 280 degrees or less."

[0330] The NILS of Example 9, formed with rhodium (Rh) with a film thickness of 33 nm and a phase difference of 240 degrees, was 2.53, and the NILS of Example 10, formed with a material containing ruthenium (Ru) and niobium (Nb) with an atomic number ratio of 85:15 and a phase difference of 240 degrees, was 2.48.

[0331] Examples 6 to 10 showed different reflectances of 2.6%, 4.4%, 9.2%, 11.0%, and 17.0%, respectively, but regardless of reflectance, better transferability than each comparative example was obtained in all cases. In this regard, it can be seen that if the reflectance is within the range of 2% or more and 20% or less, a sufficient phase shift effect is obtained and resolution is improved.

[0332] The NILS of Example 11, which was formed from a material containing ruthenium (Ru) and aluminum (Al) with an atomic ratio of 59:41 and a film thickness of 72 nm and a phase difference of 240 degrees, was 2.73. Since Example 11 has a high refractive index n of 0.94, the film thickness is thicker than that of the conventional film of Comparative Example 1 (60 nm), so the projection effect could not be reduced, but the NILS was good due to the phase shift effect.

[0333] The NILS of Example 12, formed from a material containing tin oxide (SnO) and ruthenium (Ru) with an atomic ratio of 20:80 and a phase difference of 240 degrees, is 2.78; the NILS of Example 13, formed from a material containing tin oxide (SnO) and ruthenium (Ru) with an atomic ratio of 20:80 and a phase difference of 225 degrees, is 2.65; the NILS of Example 14, formed from a material containing indium oxide (InO) and ruthenium (Ru) with an atomic ratio of 15:85 and a phase difference of 240 degrees, is 2.78; and the NILS of Example 14, formed from a material containing indium oxide (InO) and ruthenium (Ru) with an atomic ratio of 15:85 and a phase difference of 39 nm, is 240 degrees. The NILS of Example 15, which was 225 degrees, was 2.64.

[0334] In this way, even when the absorption layer (14) (absorption pattern layer (14a)) is formed with a material containing tin (Sn) or indium (In) which has excellent processability, a phase shift effect is obtained, and the resolution is improved.

[0335] The NILS of Example 16, which is formed from a material containing tantalum (Ta) and titanium (Ti) with an atomic ratio of 60:40 and a film thickness of 78 nm and a phase difference of 212 degrees, was 2.48, and the NILS of Example 17, which is formed from titanium (Ti) with a film thickness of 80 nm and a phase difference of 212 degrees, was 2.56. Since Examples 16 and 17 have relatively high refractive indices n of 0.947 and 0.952, respectively, the film thickness is thicker than that of the conventional film of Comparative Example 1 (60 nm), so the projection effect could not be reduced, but the NILS was good due to the phase shift effect. In addition, the reflectances of Examples 16 and 17 were 1.2% and 6.5%, respectively, and Example 17, which has a reflectance within the range of 2% to 20%, showed better NILS.

[0336] The NILS of Example 18, formed from a material containing molybdenum (Mo) and palladium (Pd) with an atomic ratio of 40:60 and a phase difference of 235 degrees, was 2.76, and the NILS of Example 19, formed from platinum (Pt) with a film thickness of 45 nm and a phase difference of 243 degrees, was 2.72. Both Examples 18 and 19 showed good NILS due to the phase shift effect. In addition, the reflectances of Examples 18 and 19 were 6.6% and 1.3%, respectively, and Example 18, which has a reflectance within the range of 2% to 20%, showed better NILS.

[0337] The NILS of Example 20, formed from a material containing iridium (Ir) and platinum (Pt) with an atomic ratio of 75:25 and a phase difference of 234 degrees, is 2.74; the NILS of Example 21, formed from a material containing iridium (Ir) and gold (Au) with an atomic ratio of 40:60 and a phase difference of 234 degrees, is 2.74; the NILS of Example 22, formed from a material containing rhenium (Re) and platinum (Pt) with an atomic ratio of 75:25 and a phase difference of 240 degrees, is 2.75; and the NILS of Example 23, formed from a material containing rhenium (Re) and gold (Au) with an atomic ratio of 40:60 and a phase difference of 227 degrees NILS was 2.74.

[0338] In this way, even when an absorption layer (14) (absorption pattern layer (14a)) is formed composed of elements from a third material group that has a small refractive index n and excellent processability and hydrogen resistance, a phase shift effect is obtained, and resolution is improved.

[0339] The NILS of Example 24, which is formed from a material containing platinum (Pt) and molybdenum (Mo) with an atomic ratio of 20:80 and a phase difference of 213 degrees, was 2.65, and the NILS of Example 25, which is formed from a material containing platinum (Pt) and molybdenum (Mo) with an atomic ratio of 80:20 and a phase difference of 234 degrees, was 2.74.

[0340] In addition, the NILS of Example 26, which is formed from a material containing platinum (Pt) and niobium (Nb) with an atomic ratio of 35:65 and a phase difference of 214 degrees, was 2.68, and the NILS of Example 27, which is formed from a material containing platinum (Pt) and niobium (Nb) with an atomic ratio of 80:20 and a phase difference of 234 degrees, was 2.74.

[0341] In addition, the NILS of Example 28, which is formed from a material containing gold (Au) and molybdenum (Mo) with an atomic ratio of 25:75 and a phase difference of 209 degrees, was 2.63, and the NILS of Example 29, which is formed from a material containing gold (Au) and molybdenum (Mo) with an atomic ratio of 95:5 and a phase difference of 228 degrees, was 2.75.

[0342] In addition, the NILS of Example 30, which is formed from a material containing gold (Au) and niobium (Nb) with an atomic ratio of 45:55 and a phase difference of 213 degrees, was 2.71, and the NILS of Example 31, which is formed from a material containing gold (Au) and niobium (Nb) with an atomic ratio of 90:10 and a phase difference of 234 degrees, was 2.74.

[0343] In addition, the NILS of Example 32, which is formed from a material containing gold (Au) and titanium (Ti) with an atomic ratio of 65:35 and a phase difference of 225 degrees, was 2.69, and the NILS of Example 33, which is formed from a material containing gold (Au) and titanium (Ti) with an atomic ratio of 85:15 and a phase difference of 240 degrees, was 2.75.

[0344] In addition, the NILS of Example 34, which is formed from a material containing gold (Au) and zirconium (Zr) with an atomic ratio of 70:30 and a phase difference of 218 degrees, was 2.67, and the NILS of Example 35, which is formed from a material containing gold (Au) and zirconium (Zr) with an atomic ratio of 90:10 and a phase difference of 248 degrees, was 2.74.

[0345] In addition, the NILS of Example 36, which is formed from a material containing iridium (Ir) and molybdenum (Mo) with an atomic ratio of 30:70 and a phase difference of 209 degrees, was 2.63, and the NILS of Example 37, which is formed from a material containing iridium (Ir) and molybdenum (Mo) with an atomic ratio of 90:10 and a phase difference of 227 degrees, was 2.74.

[0346] In addition, the NILS of Example 38, which is formed from a material containing iridium (Ir) and tungsten (W) with an atomic ratio of 50:50 and a phase difference of 225 degrees, was 2.69, and the NILS of Example 39, which is formed from a material containing iridium (Ir) and tungsten (W) with an atomic ratio of 90:10 and a phase difference of 240 degrees, was 2.75.

[0347] In addition, the NILS of Example 40, which is formed from a material containing iridium (Ir) and niobium (Nb) with an atomic ratio of 50:50 and a phase difference of 214 degrees, was 2.68, and the NILS of Example 41, which is formed from a material containing iridium (Ir) and niobium (Nb) with an atomic ratio of 90:10 and a phase difference of 237 degrees, was 2.76.

[0348] In addition, the NILS of Example 42, which is formed from a material containing iridium (Ir) and tantalum (Ta) with an atomic ratio of 85:15 and a phase difference of 219 degrees, was 2.71, and the NILS of Example 43, which is formed from a material containing iridium (Ir) and tantalum (Ta) with an atomic ratio of 95:5 and a phase difference of 248 degrees, was 2.74.

[0349] In addition, the NILS of Example 44, which is formed from a material containing iridium (Ir) and vanadium (V) with an atomic ratio of 65:35 and a phase difference of 201 degrees, was 2.6, and the NILS of Example 45, which is formed from a material containing iridium (Ir) and vanadium (V) with an atomic ratio of 90:10 and a phase difference of 240 degrees, was 2.75.

[0350] In addition, the NILS of Example 46, which is formed from a material containing rhenium (Re) and molybdenum (Mo) with an atomic ratio of 45:55 and a phase difference of 213 degrees, was 2.65, and the NILS of Example 47, which is formed from a material containing rhenium (Re) and molybdenum (Mo) with an atomic ratio of 90:10 and a phase difference of 234 degrees, was 2.75.

[0351] In addition, the NILS of Example 48, which is formed from a material containing rhenium (Re) and tungsten (W) with an atomic ratio of 75:25 and a phase difference of 216 degrees, was 2.71, and the NILS of Example 49, which is formed from a material containing rhenium (Re) and tungsten (W) with an atomic ratio of 95:5 and a phase difference of 227 degrees, was 2.74.

[0352] In addition, the NILS of Example 50, which is formed from a material containing rhenium (Re) and niobium (Nb) with an atomic ratio of 75:25 and a phase difference of 213 degrees, was 2.7, and the NILS of Example 51, which is formed from a material containing rhenium (Re) and niobium (Nb) with an atomic ratio of 90:10 and a phase difference of 224 degrees, was 2.74.

[0353] In this way, when an absorption layer (14) (absorption pattern layer (14a)) is formed using a material that includes elements of a fourth material group with excellent processability and hydrogen resistance in addition to elements of a third material group with a small refractive index n, a phase shift effect is obtained, and resolution is improved. In addition, when the content of elements of the third material group is 20 atomic percent or more of the total elements of the absorption layer (14), NILS is good. In addition, when the combination of elements of the third material group and the fourth material group included in the absorption layer (14) is the same, NILS is better as the content of elements of the third material group increases.

[0354] In addition, the reflective photomask blank and reflective photomask of the present disclosure are not limited to the above embodiments and examples, and various modifications are possible within a range that does not impair the features of the invention. Industrial applicability

[0355] The reflective photomask blank and reflective photomask according to the present invention can be suitably used in a manufacturing process for semiconductor integrated circuits, etc., because they form a fine pattern by EUV exposure. Explanation of the symbols

[0356] 11: Substrate 12: Reflection layer 13: Protection layer 14: Absorbent layer 14a: Absorption pattern (absorption pattern layer) 15: On the other side, challenge screen 16: Resist membrane 16a: Resist pattern 100: Reflective photomask blank 200: Reflective photomask

Claims

Claim 1 A reflective photomask blank characterized by comprising a substrate, a reflective layer that reflects EUV light having a multilayer film structure formed on the substrate, a protective layer formed on the reflective layer and protecting the reflective layer, and an absorbing layer that absorbs EUV light formed on the protective layer, wherein the absorbing layer has a phase difference within a range of 200 degrees or more and 280 degrees or less, and wherein the absorbing layer is composed of a material including RhAl, RuNb, RuAl, SnRuO, InRuO, TaTi, MoPd, IrPt, IrAu, RePt, ReAu, PtMo, PtNb, AuMo, AuNb, AuTi, AuZr, IrMo, IrW, IrNb, IrTa, IrV, ReMo, ReW, or ReNb. Claim 2 A reflective photomask blank according to claim 1, characterized in that the absorption layer has a phase difference within the range of 215 degrees or more and 270 degrees or less. Claim 3 A reflective photomask blank according to claim 1, characterized in that the absorption layer has a phase difference within a range of 230 degrees or more and 260 degrees or less. Claim 4 A reflective photomask blank according to claim 1, characterized in that the absorption layer has a refractive index n for EUV light that is less than 0.

93. Claim 5 A reflective photomask blank according to claim 1, wherein the absorption layer has a refractive index n for EUV light that is less than 0.

92. Claim 6 A reflective photomask blank according to claim 1, characterized in that the absorption layer has a reflectance of EUV light within the range of 2% or more and 20% or less. Claim 7 A reflective photomask blank according to claim 1, characterized in that the absorption layer has a reflectance to EUV light within the range of 1.2% or more and 2.4% or less, or a reflectance to EUV light within the range of 11.0% or more and 17.0% or less. Claim 8 A reflective photomask characterized by comprising a substrate, a reflective layer that reflects EUV light having a multilayer film structure formed on the substrate, a protective layer formed on the reflective layer and protecting the reflective layer, and an absorption pattern layer that absorbs EUV light having a pattern formed on the protective layer, wherein the absorption pattern layer has a phase difference within a range of 200 degrees or more and 280 degrees or less, and wherein the absorption pattern layer is composed of a material including RhAl, RuNb, RuAl, SnRuO, InRuO, TaTi, MoPd, IrPt, IrAu, RePt, ReAu, PtMo, PtNb, AuMo, AuNb, AuTi, AuZr, IrMo, IrW, IrNb, IrTa, IrV, ReMo, ReW, or ReNb. Claim 9 A reflective photomask according to claim 8, characterized in that the absorption pattern layer has a phase difference within a range of 215 degrees or more and 270 degrees or less. Claim 10 A reflective photomask according to claim 8, characterized in that the absorption pattern layer has a phase difference within a range of 230 degrees or more and 260 degrees or less. Claim 11 In claim 8, the reflection photomask is characterized in that the absorption pattern layer has a refractive index n for EUV light that is less than 0.

93. Claim 12 In claim 8, the reflection photomask is characterized in that the absorption pattern layer has a refractive index n for EUV light that is less than 0.

92. Claim 13 A reflective photomask according to claim 8, characterized in that the absorption pattern layer has a reflectance to EUV light within the range of 2% or more and 20% or less. Claim 14 A reflective photomask according to claim 8, characterized in that the absorption pattern layer has a reflectance to EUV light within the range of 1.2% or more and 2.4% or less, or a reflectance to EUV light within the range of 11.0% or more and 17.0% or less. Claim 15 delete Claim 16 delete Claim 17 delete Claim 18 delete

Citation Information

Patent Citations

  • Reflection type mask blank, reflection type mask and method for manufacturing semiconductor device

    JP2020106639A

  • Reflective mask blank for EUV lithography, reflective mask for EUV lithography, and method for manufacturing mask blank and mask

    WO2021132111A1

  • Reflective mask blank and reflective mask

    WO2021085382A1